Floral nectaries of Heliocarpus popayanensis and Luehea divaricata (Malvaceae-Grewioideae): structure and ultrastructure - Lattar, Elsa C.; Galati, Beatriz Gloria; Carrera, Constanza Soledad; Ferrucci, María S. (2018)
The structure and ultrastructure on floral nectaries of Heliocarpus popayanensis Kunth. and Luehea divaricata Mart (Malvaceae-Grewioideae) were investigated for the first time. The floral nectaries of the analysed species are structured (can be recognised macroscopically and microscopically) and of trichomatic type. Significant morphological differences were observed between the nectaries of perfect and pistillate flowers of H. popayanensis, as well as between nectaries of this species and those of the related species, Triumfetta rhomboidea Jacq. The volume of nectar produced in the perfect and pistillate flowers of H. popayanensis and in the perfect flowers of L. divaricata presents significant differences that could be related to the rewards offered to flower visitors. No differences were observed in ultrastructure features of the glandular trichomes between H. popayanensis and L. divaricata.